Oligophrenin-1 Connects Exocytotic Fusion to Compensatory Endocytosis in Neuroendocrine Cells - Houy, Sébastien (J Neurosci, 2015)
Oligophrenin-1 (OPHN1) is a protein with multiple domains including a Rho family GTPase-activating (Rho-GAP) domain, and a Bin-Amphiphysin-Rvs (BAR) domain. Involved in X-linked intellectual disability, OPHN1 has been reported to control several synaptic functions, including synaptic plasticity, synaptic vesicle trafficking, and endocytosis. In neuroendocrine cells, hormones and neuropeptides stored in large dense core vesicles (secretory granules) are released through calcium-regulated exocytosis, a process that is tightly coupled to compensatory endocytosis, allowing secretory granule recycling. We show here that OPHN1 is expressed and mainly localized at the plasma membrane and in the cytosol in chromaffin cells from adrenal medulla. Using carbon fiber amperometry, we found that exocytosis is impaired at the late stage of membrane fusion in Ophn1 knock-out mice and OPHN1-silenced bovine chromaffin cells. Experiments performed with ectopically expressed OPHN1 mutants indicate that OPHN1 requires its Rho-GAP domain to control fusion pore dynamics. On the other hand, compensatory endocytosis assessed by measuring dopamine-β-hydroxylase (secretory granule membrane) internalization is severely inhibited in Ophn1 knock-out chromaffin cells. This inhibitory effect is mimicked by the expression of a truncated OPHN1 mutant lacking the BAR domain, demonstrating that the BAR domain implicates OPHN1 in granule membrane recapture after exocytosis. These findings reveal for the first time that OPHN1 is a bifunctional protein that is able, through distinct mechanisms, to regulate and most likely link exocytosis to compensatory endocytosis in chromaffin cells.